2018
DOI: 10.1007/s11274-018-2493-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination and quantification of asiaticoside in endophytic fungus from Centella asiatica (L.) Urban

Abstract: Centella asiatica (L.) Urban is a highly considered medicinal plant owing to its secondary metabolites asiaticoside, madecassoside, asiatic acid, and madecassic acid. The asiaticoside, one of the most important constituents of the plant, is a triterpenoid saponin having memory enhancement property. Given its medicinal properties, we isolated and characterized endophytic fungi from this plant with the aim to screen these microorganisms for asiaticoside production. In total, we isolated 13 endophytic fungi from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Our results highlight the diversity of endophytic fungi in medicinal plants and their ability to synthesize bioactive secondary metabolites (Gupta et al 2018). They may also guide new approaches to synthesize dipsacus saponin VI from D. asperoides , permitting sustainable development of this important traditional Chinese medicine resource.…”
Section: Discussionsupporting
confidence: 70%
“…Our results highlight the diversity of endophytic fungi in medicinal plants and their ability to synthesize bioactive secondary metabolites (Gupta et al 2018). They may also guide new approaches to synthesize dipsacus saponin VI from D. asperoides , permitting sustainable development of this important traditional Chinese medicine resource.…”
Section: Discussionsupporting
confidence: 70%
“…Schistosomiasis is a fatal disease that threatens human health, and more than 150 million people are infected with schistosomiasis globally (Bylka et al, 2014;Zhou et al, 2016;Fitri et al, 2018a). Previous studies showed that liver fibrosis symptoms due to S. japonicum can persist for a long time after complete disinfestation (Fitri et al, 2018b;Song et al, 2018;He et al, 2019). Patients with advanced schistosomiasis-induced liver fibrosis gradually develop cirrhosis due to egg deposition, and often die of gastrointestinal bleeding and liver failure caused by portal hypertension (Barnett, 2018;Chuah et al, 2019;Lewis and Tucker, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Inaccurate results of these tests usually resulted in wrong isolation and characterization. Development of molecular biology tools have facilitated the isolation and identification of pyrethroid degrading microbes (16S rRNA for bacteria and ITS sequencing for fungi) (Gangola et al, 2018; Gupta et al, 2018). Degradation of pyrethroids is commonly analyzed by chromatographic techniques such as high performance liquid chromatography (HPLC), gas chromatography (GC), and mass spectroscopy (MS) (Castellarnau et al, 2016).…”
Section: Recent Tools For Pyrethroid Biodegradationmentioning
confidence: 99%